Adakah Pengaruh Pertumbuhan Ekonomi terhadap Pendapatan Asli Daerah? - Fadli, Faishal (Jurnal Ilmu Ekonomi dan Pembangunan, 2016)
The implementation of regional autonomy resulted in each region to be able to manage their finances independently. This is one way the central government to remove the dependency of local governments to the central government. Thus requiring local governments to explore the sources of local revenue in order to finance regional development. In an effort to increase local revenues derived from the PAD is determined by economic factors or economic potential which has the prospect to be developed for each area. While the economic progress of a region heavily dependent on the development efforts undertaken by the government in providing public facilities to support economic activity. so it needs to be studied further economic growth in East Java, which increased from year to year, is also accompanied by an increase in revenue (PAD) as one source of income in financing regional development. The result indicates the role of the revenue (PAD) in the Regional Budget (APBD) of East Java Province indicates that there is still very small, with an average of 15.47% of the total revenue budget. This means that the level of dependence of local governments on the central government is still high. Although the results of regional revenue projections indicate that component has been great in their contribution of the reception area, which amounted to 69.52%. Using the ordinary least squre method, the result of regression correlation are insignificant. This means that the regional gross domestic product does not have an effect on revenue of East Java Province. If an increase or decrease in regional gross domestic product will not increase or decrease revenue amount. This means that there is no significant relationship between economic growths towards the reception of the revenue. Keywords: economic growth, revenues (PAD), Regional Budget (APBD), Gross Domestic Product (GDP).